THE HUYGENS-HELLAS GIANT DIKE SYSTEM ON MARS: IMPLICATIONS FOR LATE NOACHIAN-EARLY HESPERIAN VOLCANIC RESURFACING AND CLIMATIC EVOLUTION - Head J.W.; Dickson J.; Wilson L.; Neukum G. (My University, 2006)
Two narrow, broadly arcuate, low ridges extend for 600-700 km in western Terra Tyrrhena, Mars, crosscut ancient Noachian terrain, and are associated with Early Hesperian plains, which cover ~30% of Mars. Geological relationships suggest that the ridges represent near-surface erosional remnants of subsurface dikes, solidified magma-filled cracks that were responsible for the volcanic emplacement of the plains. Ridge width and geometry are consistent with very high-effusion-rate flood basalt eruptions, emplacement events that would form smooth featureless plains and input significant volcanic gas into the atmosphere. Geological relationships suggest that the ridges were exposed by erosion (fluvial, sublimation, eolian) and partial removal of a regional volatile-rich dust layer. © 2006 Geological Society of America.
Keywords: DIKE; ERUPTIONS; HESPERIAN; MAGMA; MARS; NOACHIAN